The impact of mini-educational games on learning the basic skills of football - Khadar , Khaled; Khouildi , Elhouari; Bensaid , Mahmoud (sports creativity, 2025)
We adopted in the study of mini-educational games as a modern educational method that helps in the development of basic skills, especially at this sensitive age (11 - 13) years, which distinguishes the child with skillful preparations to grow and develop, by studying the actual practice of the method of mini-football during training sessions and make our study a reference for researchers In the sports field Through the research results, we have extended an annual program for teaching basic skills -Include the method of mini-educational games as a very important way to achieve the training session. - Basic skills must be taught during this period, because the child at this stage have the ability and rapid